The effects of artificial intelligence on artistic production and its role in the field of art education - أمين, د. كوسار رشيد (Sulaimani Journal for Humanities, 2025)
With the evolution of Artificial Intelligence (AI) systems, their impact has rapidly grown in recent decades, now extending to one of humanity's most original activities: the fields of art and art education. Due to this technological shock, education systems worldwide have undergone fundamental changes. One area that has been less researched but is profoundly affected by this technology is art education and the production of artistic works. With the help of algorithms, artificial intelligence can contribute to composing poetry, inventing music, painting artistic canvases, and all other fields of art. From this, it becomes clear that the relationship between humans and machines, and humans and art, has brought about a complete change in the fundamental principles of art. This research was conducted using a descriptive-analytical approach and is generally composed of three main sections: The first section consists of several topics such as introducing AI and its effects on the production of artistic works in all their various forms. The second section comprises other topics, including an introduction to the fields of education and art education, and the role of artificial intelligence in art education. The third section discusses the challenges that artistic works and the art education process face due to the advent of artificial intelligence, along with proposed solutions. The results of this study show that by centering humanity and preserving the creative nature of humans, artificial intelligence can become a powerful tool for enhancing quality and bringing about significant changes in art education and artistic production. Finally, it is predicted that the future of artificial intelligence will lead to a blend of human intelligence and artificial intelligence in education and the production of artistic works.
Keywords: Artificial Intelligence; Algorithms Art; Art Education Artwork; the Future of Art